AKSARA JAWI DAN NARASI SOSIAL : MENELUSURI BAHASA DALAM BUDAYA MELAYU - Nabila Meiliza Damanik; Sri Mawaddah (EDUCATIONAL JOURNAL : General and Specific Research, 2025)
This paper explores the role of the Jawi script as a cultural heritage that functions not only as a writing system but also as a medium of social narrative within the Malay community. The study adopts a qualitative approach, incorporating both sociolinguistic and historical methods to trace the development of the Jawi script, its functions in social life, and efforts to preserve it within the context of Malay culture. The findings reveal that Jawi played a crucial role in the dissemination of knowledge, the construction of identity, and the preservation of Islamic values in the Nusantara region. The social narratives embedded in Jawi texts reflect the thoughts, values, and societal structures of traditional Malay society. Jawi script served not only as a tool for communication but also as a medium for conveying religious knowledge, customs, and political discourse in the past. It shaped and sustained the community's understanding of its own identity, making it a key component in the formation of the collective Malay-Islamic discourse. However, the forces of modernization, changes in the education system, and the dominance of the Romanized (Rumi) script have led to a significant decline in Jawi usage, especially among the younger generation. Therefore, ongoing and future efforts—particularly in education, digitization, and cultural promotion—are essential to ensure the continued relevance and survival of the Jawi script as a vital element of Malay identity that deserves to be preserved and strengthened over time.